Les collections du Panthéon. Étude, inventaire et perspectives scientifiques - Élisabeth Portet (In Situ)
The Centre des monuments nationaux is responsible for the management, promotions and interpretation of the collections of the Panthéon, which have been the subject of an inventory campaign undertaken from 2005. The data collected gives us better information about the moveable heritage present in the monument (637 items listed) and allows for conservation interventions to be properly planned with a view to interpreting the objects for the public at large. The methods used to carry out this mission, which was completed in 2016, and the first results of the undertaking are presented in this article which also gives consideration to the archaeological and fragmentary perception of the corpus constituted.